Exploring the predictive factors in the gastrointestinal involvement of patients with immunoglobulin A vasculitis - Betül Öksel; Nihal Şahin; Hafize Emine Sönmez (The Turkish Journal of Pediatrics)
Background. Immunoglobulin A vasculitis (IgAV), the most common systemic vasculitis in children, typically presents with gastrointestinal (GI) symptoms in about half of cases. This study aimed to analyze the clinical and laboratory findings of patients with IgAV regarding GI involvement.